Intelligent Analysis of Logistics Information Based on Network Dynamic Data - Honglin Yan (Journal of Control Science and Engineering)
Based on the concept of market sharing, the author has developed Internet technology-based logistics distribution data exchange to control the cost of shipping to benefit the transfer for new types of management and operations. Investigate the needs of export shipments, such as external management responsibilities, requirements of management responsibilities, data recovery, and data recovery requirements, based on the current state of the shared platform model integration, and determine the business model. Based on this, three types of IoT cloud, such as single-center multiterminal, multicenter multiterminal, and data and application layer, can be completed and the Internet of Things can be defined by education. About the use of the cost of distribution, the transportation contract is to identify the needs of Internet technology-based logistics distributions and complete the construction of Internet technology-based logistics distribution information exchange platform. The results of the experiment showed that the results recorded in the test group did not differ from the actual results only twice, the level of difference was small, and the mean error was less than 1%. In terms of logistics distribution exposure, the average level of the assessment group is significantly higher than that of the management group, with a minimum collection rate of 90.07%, while the minimum value of the control group is as low as 76.32%. Compared with blockchain-based integration, Internet of Things technology-enabled sharing platforms can capture real-time data, transfer data, monitor shipping costs, and improve management and operations.